IMPROVING THE ECONOMIC ASSESSMENT OF FIXED ASSETS IN RAILWAY TRANSPORT ENTERPRISES - Boliyev Alisher Sobirjonovich,Fayzullayev Javlonbek Sultonovich (Ethiopian International Journal of Multidisciplinary Research, 2025)
The railway sector plays a strategic role in Uzbekistan’s economic infrastructure, ensuring large-scale cargo and passenger transportation. Efficient management of railway enterprises depends largely on the rational use and timely renewal of fixed assets. This paper analyzes the existing approaches to the economic assessment of fixed assets in railway transport, identifies shortcomings, and proposes directions for improvement. A modernized assessment framework is essential for enhancing investment attractiveness, ensuring financial sustainability, and aligning asset management with global best practices.